Interaction with Decay-Accelerating Factor Facilitates Coxsackievirus B Infection of Polarized Epithelial Cells - Shieh, Joseph T. C. (American Society for Microbiology, 2002)
All coxsackie B (CB) viruses can initiate infection by attaching to the coxsackievirus and adenovirus receptor (CAR). Although some CB isolates also bind to decay-accelerating factor (DAF), the role of DAF interaction during infection remains uncertain. We recently observed that CAR in polarized epithelial cells is concentrated at tight junctions, where it is relatively inaccessible to virus. In the experiments reported here we found that, unlike CAR, DAF was present on the apical surface of polarized cells and that DAF-binding isolates of CB3 and CB5 infected polarized epithelial cells more efficiently than did isolates incapable of attaching to DAF. Virus attachment and subsequent infection of polarized cells by DAF-binding isolates were prevented in the presence of anti-DAF antibody. Serial passage on polarized cell monolayers selected for DAF-binding virus variants. Taken together, these results indicate that interaction with DAF on the apical surface of polarized epithelial cells facilitates infection by a subset of CB virus isolates. The results suggest a possible role for DAF in infection of epithelial cells at mucosal surfaces.